What Are You Going Through?: Practices of Care, Emotional Literacy and Visual Literacy in Jöns Mellgren’s Sigrid och natten - Stoll, Mareike (Barnboken, 2023)
Jöns Mellgren’s Sigrid och natten (Sigrid and the Night, 2013), is a tale of grief and post-traumatic stress, but also – and more importantly – a tale of care and healing. The article’s aim is to show how the book offers narrative-visual access to social emotions (such as love and grief) and mental states (such as depression), which are usually not yet accessible to a young audience through their own experience. These social emotions and mental states are made tangible in different ways through the multimediality and materiality of the picturebook, and by the particular dialogical reading situation that the picturebook warrants. Picturebooks are consequently understood as part of visual literacy training and, explicitly in this context, of the acquiring of “emotional literacy” (Nikolajeva, “Emotions in Picturebooks” 114). The article argues that Sigrid och natten provides a training ground for visual and, in particular, emotional literacy. Three leitmotifs are examined in Sigrid och natten, namely lighthouses, colors, and hands, and one particular question is used as an analytical tool: “what are you going through?” (Ruddick, “Maternal Thinking” 596). The theme of mothering is connected to the hand and the lighthouse in particular. Regarded in a larger context of practices of care, a form of mothering takes place, for instance, in the reading situation (the reading aloud) of the book by caretakers/readers. The concept of visual literacy is influenced by Walter Benjamin’s theory on picturebooks, while cognitive criticism, reader-response theory, and a material and visual studies approach provide the theoretical framework for the reading of Mellgren’s picturebook.